Self-adhesion composite patch for tooth extraction cavity wound repair and preparation method thereof
The wound filling layer and adhesive barrier layer design of the self-adhesive composite patch solves the problems of poor hemostasis and foreign body barrier of existing extraction socket repair materials, and achieves a multi-functional repair effect of rapid hemostasis, no need for secondary surgery, and no impact on healing.
Patent Information
- Application Number
- CN202510510108.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-09-05
AI Technical Summary
Existing tooth extraction socket repair materials have problems such as poor hemostatic effect, non-degradability or long degradation time, impact on wound healing, and inability to effectively block foreign matter.
A self-adhesive composite patch is used, including a wound filling layer and an adhesive barrier layer. The wound filling layer is made of cross-linked gelatin aerogel with high porosity and water absorption. The adhesive barrier layer is composed of polymer fibers and biological glue to form a nano-scale fiber network to achieve hemostasis and wound closure.
It achieves rapid hemostasis, eliminates the need for secondary surgery for removal, does not affect wound healing, and effectively blocks foreign matter. It has good biosafety and degradability, and provides multi-functional wound repair effects.
Smart Images

Figure CN120586141A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedical materials, and in particular relates to a self-adhesive composite patch for repairing tooth extraction socket wounds and a preparation method thereof. Background Art
[0002] Currently, the materials used for tooth extraction socket repair on the market are mainly divided into two types in terms of their function: filling type and covering type. Filling materials usually exert their hemostatic effect by mechanically compressing the bleeding area. For example, for conventional tooth extraction sockets, cotton strips or gauze are often used in clinical treatment to stop bleeding by pressing or biting. Iodoform gauze is another commonly used extraction socket filling and hemostatic material. Iodoform gauze has the characteristics of soft texture and strong plasticity, which makes it easy to fill the entire extraction socket after tooth extraction surgery. The free iodide ions dissolved from the gauze after filling have certain bactericidal and anti-infection capabilities.
[0003] In addition, sponge-like materials are currently used for filling and repairing extraction sockets. Their main ingredients are gelatin, oxidized cellulose, chitosan, and collagen. These sponge-like filling materials generally have a porous structure and can quickly absorb blood from the extraction socket, promoting platelet aggregation and achieving hemostasis.
[0004] Covering materials typically don't have a hemostatic effect. Their primary function is to prevent foreign matter, such as food particles, from entering the extraction socket, thereby preventing local discomfort or inflammation caused by such foreign matter. These covering materials are often composed of natural resins, silicone rubber, or other composite materials, and possess a certain degree of adhesion, sealing the extraction wound through covering.
[0005] In the prior art, hemostatic filling materials, such as cotton strips, gauze, and iodoform gauze, are non-degradable in the extraction socket and require a secondary surgical procedure to remove. For sockets with severe bleeding or when the hemostatic effect is unclear, multiple removals may be necessary, significantly delaying socket wound healing. In particular, although the addition of iodide to iodoform gauze improves its anti-infective properties, it is irritating to the oral cavity after filling, making it difficult for doctors and patients to accept. Sponge-like filling materials, primarily composed of gelatin, oxidized cellulose, chitosan, and collagen, require large quantities of material to fill the extraction socket. However, these materials often swell when absorbing liquid, which can affect wound healing. When some affected teeth are in close proximity to the mandibular nerve canal, overfilling with sponge-like materials can also cause localized abnormalities due to nerve compression. Sponge-like filling materials often maintain their stability in the extraction socket by increasing the degree of crosslinking, but this prolongs the material's in vivo degradation time, impacting alveolar bone repair. Furthermore, the introduction of chemical crosslinkers introduces uncertainty into the wound healing process. In addition, covering materials made of natural resin, silicone rubber or other composite materials generally can only seal the tooth extraction wound, and have almost no hemostatic and repairing effects on the tooth extraction socket. Summary of the Invention
[0006] Based on the above technical background, the main purpose of the present invention is to provide a self-adhesive composite patch for tooth extraction socket wound repair and a preparation method thereof, so as to overcome the shortcomings of the prior art.
[0007] To achieve the aforementioned object of the invention, the technical solutions adopted by the present invention include: The first aspect of the present invention is to provide a self-adhesive composite patch for repairing tooth extraction socket wounds, the self-adhesive composite patch comprising a wound filling layer and an adhesive barrier layer, the wound filling layer being bonded to the middle of the upper surface of the adhesive barrier layer, the wound filling layer being made of a biological sponge material, and the adhesive barrier layer being made of polymer fibers and biological glue, such as Figure 1 shown.
[0008] Preferably, the raw materials for preparing the biological sponge material are selected from one or more of oxidized cellulose, chitosan, starch, polyethylene glycol, polyvinyl alcohol, collagen, gelatin, and tannic acid; and / or, The polymer fiber is made of one or more raw materials selected from polycaprolactone, polylactic acid, polylactic acid-glycolic acid copolymer, polyethylene glycol-caprolactone copolymer, polyamino acid, and polyurethane; and / or, The biological glue is prepared from one or more raw materials selected from oxidized cellulose, chitosan, starch, polyethylene glycol, polyvinyl alcohol, collagen, gelatin and tannic acid.
[0009] More preferably, the biological sponge material is made of gelatin and tannic acid; and / or, The polymer fiber is made of polycaprolactone; and / or, The biological glue is prepared from gelatin and tannic acid.
[0010] The second aspect of the present invention is to provide a method for preparing the self-adhesive composite patch for repairing tooth extraction socket wounds according to the first aspect of the present invention, the preparation method comprising: The biosponge material is made into a wound filling layer, polymer fibers are stacked into a polymer fiber membrane material, and bioglue is coated on the surface of the polymer fiber membrane material to obtain an adhesive barrier layer. The wound filling layer is bonded to the middle of the adhesive barrier layer and then vacuum dried for 10 to 15 hours to obtain a self-adhesive composite patch.
[0011] Preferably, the method for preparing the wound filling layer comprises the following steps: Gelatin is dissolved in reverse osmosis water at 55-65°C in a water bath with a gelatin mass fraction of 1%-8%. An alkaline solution is added to adjust the pH, and then tannic acid is added and stirred at 40-50°C in a water bath for 0.5-2 hours to carry out a cross-linking reaction to obtain a cross-linked gelatin solution. The mass ratio of gelatin to tannic acid is 1:(0.05-0.10). The cross-linked gelatin solution is then placed in a mold, cooled to room temperature, and frozen at -10--25°C. Finally, it is freeze-dried for 20-30 hours to obtain a gelatin-based porous bio-sponge material, i.e., a wound filling layer.
[0012] Preferably, the method for preparing the adhesive barrier layer comprises the following steps: Step 1: adding polycaprolactone to a solvent and mixing them uniformly to obtain a polycaprolactone solution, and electrospinning the polycaprolactone solution to obtain a polymer fiber membrane material; Step 2: Dissolve gelatin in reverse osmosis water, then add alkaline solution to adjust the pH, and then add tannic acid to carry out a cross-linking reaction to obtain a cross-linked gelatin solution. Apply the cross-linked gelatin solution to the surface of the polymer fiber membrane material, and after cooling, obtain a sticky barrier layer.
[0013] In step 1, Preferably, polycaprolactone is added to ethyl acetate and mixed evenly to obtain a polycaprolactone solution with a mass concentration of 15 to 25%. The polycaprolactone solution is electrospun to obtain polymer fibers with a length of 100 nm to 500 nm. The polymer fibers are stacked on a receiving device to form a PCL polymer fiber membrane material.
[0014] Preferably, the electrospinning conditions are: voltage 10-20 kV, receiving distance 10-20 cm, and liquid feeding speed 0.5-1.5 mL / h.
[0015] In step 2, Preferably, gelatin is dissolved in reverse osmosis water in a water bath at 55 to 65° C., with a gelatin mass fraction of 3% to 7%. An alkaline solution is then added to adjust the pH to 9 to 10.5, followed by addition of tannic acid, which is stirred and reacted for 0.5 to 2 hours in a water bath at 40 to 50° C. The mass ratio of gelatin to tannic acid is 1:(0.05 to 0.10), to obtain a cross-linked gelatin solution.
[0016] Preferably, the cross-linked gelatin solution is evenly coated on the surface of the polymer fiber membrane material, and placed at 0-4° C. to allow the cross-linked gelatin solution to cool on the fiber membrane surface to form a gel, thereby obtaining a sticky barrier layer.
[0017] The beneficial effects of the present invention are: (1) The self-adhesive composite patch for tooth extraction socket wound repair described in the present invention comprises a wound filling layer and an adhesive barrier layer. The wound filling layer is located between the adhesive barrier layer. The biological sponge material used in the wound filling layer is cross-linked gelatin aerogel. The cross-linked gelatin aerogel has the characteristics of ultra-high porosity and strong water absorption, so that the cross-linked gelatin aerogel can achieve a hemostatic function with a small amount of filling. It can quickly absorb blood in the tooth extraction socket and achieve a hemostatic function after tooth extraction surgery by promoting the formation of the body's own blood clots. At the same time, the biological sponge material can fall off from the adhesive barrier layer and completely degrade within one week, eliminating the need for a secondary surgical removal. In addition, due to the reduced filling amount of the biological sponge material and its excellent degradation performance, it will not affect wound healing.
[0018] (2) The adhesive barrier layer is composed of polymer fibers and biological glue, and the biological glue is evenly coated on the surface of the fiber membrane material obtained by stacking the polymer fibers. The present invention processes the adhesive barrier layer into a dense stacked network structure composed of nano-scale fibers and adheres it to the surface of the tooth extraction wound (such as Figure 2 (as shown in the figure), effectively isolates the alveolar socket from the oral cavity, creating a relatively closed wound healing environment. The wound filling layer, located between the adhesive barrier layer and the surface of the extraction wound, prevents oral food debris and small foreign matter from entering the socket, thereby, to a certain extent, preventing postoperative socket inflammation. The dense nanofiber network obtained from polymer processing exhibits excellent flexibility, barrier properties, air permeability, and hydrophobicity, surpassing the performance of existing covering materials such as resins and silicone rubber.
[0019] (3) Compared with the existing simple filling or covering materials on the market, the self-adhesive composite patch of the present invention not only has the multiple functions of hemostasis, repair and barrier, but also has good biosafety, degradability and intraoperative operability, making it have a good prospect in the field of tooth extraction socket wound repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic structural diagram of the self-adhesive composite patch is shown; Figure 2 A schematic diagram showing the use of the self-adhesive composite patch for tooth extraction socket wound repair; Figure 3 Shown is a photograph of the biological sponge material prepared in Example 1; Figure 4 The photographs of the biological sponge material prepared in Example 1 after absorbing water for 1 second and 10 seconds are shown; Figure 5 A photograph of the self-adhesive composite patch prepared in Example 1 is shown. DETAILED DESCRIPTION
[0021] The present invention will be described in detail below, and the characteristics and advantages of the present invention will become clearer and more distinct with the following description.
[0022] The first aspect of the present invention is to provide a self-adhesive composite patch for repairing tooth extraction socket wounds, the self-adhesive composite patch comprising a wound filling layer and an adhesive barrier layer, the wound filling layer being bonded to the middle of the upper surface of the adhesive barrier layer, the wound filling layer being made of a biological sponge material, and the adhesive barrier layer being made of polymer fibers and biological glue, such as Figure 1 shown.
[0023] Preferably, the shape of the wound filling layer is not limited. More preferably, the wound filling layer is cylindrical with a height of 3 to 5 mm and a diameter of 1 to 1.5 cm.
[0024] Preferably, the adhesive barrier layer is rectangular, 4 cm in length, 1.5 to 2 cm in width, and 1 to 3 mm in thickness.
[0025] The raw materials for preparing bio-glue are the same as those for preparing bio-sponge materials, except that the preparation process, microscopic physical structure and properties are different.
[0026] The raw materials for preparing the biological sponge material are selected from one or more of oxidized cellulose, chitosan, starch, polyethylene glycol, polyvinyl alcohol, collagen, gelatin, and tannic acid, and the raw materials have the function of absorbing water and stopping bleeding.
[0027] Preferably, the biological sponge material is made of gelatin and tannic acid.
[0028] The polymer fiber is made of one or more raw materials selected from polycaprolactone (PCL), polylactic acid (PLA), polylactic acid-glycolic acid copolymer (PLGA), polyethylene glycol-caprolactone copolymer (PEG-PCL), polyamino acid (PAA), and polyurethane (PU), which also have certain hydrophobicity, good biocompatibility and degradability.
[0029] Preferably, the polymer fibers are made from polycaprolactone.
[0030] The raw materials for preparing the bio-glue are selected from one or more of oxidized cellulose, chitosan, starch, polyethylene glycol, polyvinyl alcohol, collagen, gelatin and tannic acid.
[0031] Preferably, the bioglue is made from gelatin and tannic acid.
[0032] The second aspect of the present invention is to provide a method for preparing the self-adhesive composite patch for repairing tooth extraction socket wounds according to the first aspect of the present invention, the preparation method comprising the following steps: The biosponge material is made into a wound filling layer, the polymer fibers are stacked into a polymer fiber membrane material, the bioglue is coated on the surface of the polymer fiber membrane material to obtain an adhesive barrier layer, the wound filling layer is bonded to the middle of the upper surface of the adhesive barrier layer, and then vacuum dried for 10 to 15 hours, preferably vacuum dried for 12 hours, to obtain a self-adhesive composite patch.
[0033] Preferably, the preparation method comprises the following steps: bonding the wound filling layer to the middle position of the bioglue coated on the surface of the polymer fiber membrane material, such as Figure 1 As shown, the self-adhesive composite patch is obtained by vacuum drying for 10 to 15 hours, preferably vacuum drying for 12 hours.
[0034] The preparation method of the wound filling layer comprises the following steps: Gelatin is dissolved in reverse osmosis water at 55-65°C in a water bath with a gelatin mass fraction of 1%-8%. An alkaline solution is added to adjust the pH, and then tannic acid is added and stirred at 40-50°C in a water bath for 0.5-2 hours to carry out a cross-linking reaction to obtain a cross-linked gelatin solution. The mass ratio of gelatin to tannic acid is 1:(0.05-0.10). The cross-linked gelatin solution is then placed in a mold, cooled to room temperature, and frozen at -10--25°C. Finally, it is freeze-dried for 20-30 hours to obtain a gelatin-based porous bio-sponge, i.e., a wound filling layer.
[0035] Preferably, gelatin is dissolved in reverse osmosis water in a water bath at 60°C, with a mass fraction of gelatin of 5%. Sodium hydroxide solution is added to adjust the pH to 10, and then tannic acid is added and stirred in a water bath at 45°C for 1 hour to carry out a cross-linking reaction to obtain a cross-linked gelatin solution. The mass ratio of gelatin to tannic acid is 1:0.08. The cross-linked gelatin solution is then placed in a mold, cooled to room temperature, and frozen at -20°C. Finally, it is freeze-dried for 24 hours to obtain a gelatin-based porous biological sponge, i.e., a wound filling layer.
[0036] The method for preparing the sticky barrier layer comprises the following steps: Step 1: adding polycaprolactone to a solvent and mixing them uniformly to obtain a polycaprolactone solution, and electrospinning the polycaprolactone solution to obtain a polymer fiber membrane material; Step 2: Dissolve gelatin in reverse osmosis water, then add alkaline solution to adjust the pH, and then add tannic acid to carry out a cross-linking reaction to obtain a cross-linked gelatin solution. Apply the cross-linked gelatin solution to the surface of the polymer fiber membrane material, and after cooling, obtain a sticky barrier layer.
[0037] In step 1, polycaprolactone is added to ethyl acetate and mixed evenly to obtain a polycaprolactone solution with a mass concentration of 15-25%. The polycaprolactone solution is electrospun to obtain polymer fibers with a length of 100 nm to 500 nm. The polymer fibers are freely stacked on a receiving device to form a PCL polymer fiber membrane material.
[0038] Preferably, the mass concentration of the polycaprolactone solution is 20%.
[0039] The electrospinning conditions are: voltage 10-20 kV, receiving distance 10-20 cm, and liquid feeding speed 0.5-1.5 mL / h, where the receiving distance refers to the distance between the spinneret and the receiving device.
[0040] Preferably, the electrospinning conditions are: voltage 15 kV, receiving distance 15 cm, and liquid feeding speed 1.0 mL / h.
[0041] The basic principle of electrospinning is: a strong electrostatic field is generated between the spinneret and the receiving device. The droplets at the nozzle outlet are acted upon by the Coulomb force in the electrostatic field, and their surface charges are repelled. The polymer solution is pulled to form polymer fibers due to its high viscosity and entanglement between molecular chains.
[0042] In step 2, gelatin is dissolved in reverse osmosis water in a water bath at 55 to 65° C., with a mass fraction of gelatin of 3% to 7%. An alkaline solution is then added to adjust the pH to 9 to 10.5. Tannic acid is then added and stirred in a water bath at 40 to 50° C. for 0.5 to 2 hours. The mass ratio of gelatin to tannic acid is 1:(0.05 to 0.10), thereby obtaining a cross-linked gelatin solution.
[0043] Preferably, gelatin is dissolved in reverse osmosis water in a water bath at 60°C, with a gelatin mass fraction of 5%, and then an alkaline solution is added to adjust the pH to 10, followed by adding tannic acid and stirring the mixture in a water bath at 45°C for 1 hour, with a mass ratio of gelatin to tannic acid of 1:0.08, to obtain a cross-linked gelatin solution.
[0044] A cross-linked gelatin solution is evenly applied to the surface of the polymer fiber membrane material. The cross-linked gelatin solution is then cooled at 0-4°C to form a gel on the fiber membrane surface, thereby obtaining a PCL polymer fiber membrane with tissue adhesion properties, i.e., an adhesive barrier layer. Alternatively, the PCL polymer fiber membrane can be directly immersed in the cross-linked gelatin solution for a certain period of time to obtain a polymer fiber membrane with tissue adhesion properties.
[0045] Preferably, the cross-linked gelatin solution is evenly coated on the surface of the polymer fiber membrane material, and placed at 4°C to allow the cross-linked gelatin solution to cool and form a gel on the fiber membrane surface to obtain a PCL polymer fiber membrane with tissue adhesion properties, that is, an adhesive barrier layer.
[0046] Example The present invention is further described below by way of specific examples, which are intended to illustrate the present invention but not to limit the scope of the present invention. The raw materials used in the examples of the present invention were all purchased.
[0047] Example 1 The preparation process of the biological sponge material is as follows: Biomedical-grade gelatin was dissolved in reverse osmosis (RO) water at a mass fraction of 5% in a 60°C water bath. After the gelatin was completely dissolved, the pH of the solution was adjusted to 10 using sodium hydroxide (NaOH). Tannic acid (0.64%) was then added to the gelatin solution and stirred in a 45°C water bath for 1 hour to crosslink the gelatin. The gelatin-to-tannic acid mass ratio was 1:0.08. The crosslinked gelatin solution was poured into a mold (a cylindrical cavity with a radius of 0.75 cm and a height of 0.5 cm), cooled to room temperature, and then frozen at -20°C. The frozen crosslinked gelatin was freeze-dried for 24 hours to produce a gelatin-based porous biosponge. Figure 3 As shown, the photos of the biological sponge material after absorbing water for 1s and 10s are as follows Figure 4 As shown, from Figure 4 It can be seen that the biological sponge material prepared by the present invention has excellent water absorption.
[0048] The preparation process of the sticky barrier layer is as follows: 1) The polymer fibers used in the adhesive barrier layer were prepared by electrospinning a 20% (mass) polycaprolactone (PCL) solution under conditions of high voltage (15 kV), a receiving distance of 15 cm, and a liquid feed rate of 1.0 mL / h. Due to the high viscosity and entanglement between the molecular chains of the 20% PCL solution, polymer fibers with lengths ranging from 100 nm to 500 nm were formed. The PCL solution was prepared using analytically pure (AR) grade ethyl acetate. The fibers formed a PCL polymer fiber membrane by free accumulation on the receiving device. The membrane was then cut into rectangular shapes 4 cm long and 2 cm wide.
[0049] 2) Modification of the bioglue in the adhesive barrier layer: Biomedical-grade gelatin was dissolved in reverse osmosis (RO) water at a mass fraction of 5% in a 60°C water bath. After complete dissolution, the pH of the solution was adjusted to 10 using sodium hydroxide (NaOH). Tannic acid (0.64% by mass / volume) was then added to the gelatin solution. The solution was stirred in a 45°C water bath for 1 hour to produce a cross-linked gelatin solution with a gelatin:tannic acid mass ratio of 1:0.08. After the cross-linked gelatin solution cooled to room temperature, it was evenly coated onto the surface of the prepared PCL polymer fiber membrane. The cross-linked gelatin solution was then allowed to cool at 4°C to form a gel on the membrane surface, resulting in a PCL polymer fiber membrane with tissue adhesion properties.
[0050] Taking advantage of the adhesiveness of the gel on the surface of the polymer fiber membrane, the previously prepared gelatin-based porous bio-sponge was directly bonded to the center of the gelatin coating layer of the fiber membrane, and then dried in a vacuum drying oven for 12 hours to obtain the desired self-adhesive composite patch, as shown in the photo. Figure 5 shown.
[0051] Example 2 The preparation process of the biological sponge material is as follows: Biomedical-grade gelatin was dissolved in reverse osmosis (RO) water at a mass fraction of 1% in a 55°C water bath. After complete dissolution, the pH of the solution was adjusted to 10 using sodium hydroxide (NaOH). Tannic acid was then added to the gelatin solution and stirred in a 40°C water bath for 2 hours to crosslink the gelatin. The gelatin-to-tannic acid mass ratio was 1:0.05. The cross-linked gelatin solution was poured into a mold (a cylindrical cavity with a radius of 0.75 cm and a height of 0.5 cm), cooled to room temperature, and then frozen at -10°C. Finally, the frozen cross-linked gelatin was freeze-dried for 30 hours to produce a gelatin-based porous biosponge.
[0052] The preparation process of the sticky barrier layer is as follows: 1) The polymer fibers used in the adhesive barrier layer were prepared by electrospinning a 15% (mass) polycaprolactone (PCL) solution under conditions of high voltage (10 kV), a receiving distance of 10 cm, and a liquid feed rate of 0.5 mL / h. Due to the high viscosity and entanglement between the molecular chains of the 15% PCL solution, polymer fibers with lengths ranging from 100 nm to 500 nm were formed. The PCL solution was prepared using analytically pure (AR) grade ethyl acetate. The fibers formed a PCL polymer fiber membrane by free deposition on the receiving device. The membrane was then cut into rectangular shapes 4 cm long and 2 cm wide.
[0053] 2) Modification of the bioglue in the adhesive barrier layer: Biomedical-grade gelatin was dissolved in reverse osmosis (RO) water at a mass fraction of 3% in a 55°C water bath. After complete dissolution, the pH of the solution was adjusted to 9 using sodium hydroxide (NaOH). Tannic acid was then added to the gelatin solution, and the mixture was stirred in a 40°C water bath for 2 hours to produce a cross-linked gelatin solution with a gelatin:tannic acid mass ratio of 1:0.05. After the cross-linked gelatin solution cooled to room temperature, it was evenly coated onto the surface of the prepared PCL polymer fiber membrane. The cross-linked gelatin solution was then placed at 0°C to cool and form a gel on the fiber membrane surface, resulting in a PCL polymer fiber membrane with tissue adhesion properties.
[0054] Taking advantage of the adhesiveness of the gel on the surface of the polymer fiber membrane, the previously prepared gelatin-based porous bio-sponge was directly bonded to the center of the gelatin coating layer of the fiber membrane, and then dried in a vacuum drying oven for 10 hours to obtain the desired self-adhesive composite patch. Example 3 The preparation process of the biological sponge material is as follows: Biomedical-grade gelatin was dissolved in reverse osmosis (RO) water at a mass fraction of 8% in a 65°C water bath. After complete dissolution, the solution pH was adjusted to 10 using sodium hydroxide (NaOH). Tannic acid was then added to the gelatin solution and stirred in a 50°C water bath for 0.5 hours to crosslink the gelatin. The gelatin-to-tannic acid mass ratio was 1:0.1. The cross-linked gelatin solution was poured into a mold (a cylindrical cavity with a radius of 0.75 cm and a height of 0.5 cm), cooled to room temperature, and then frozen at -25°C. Finally, the frozen cross-linked gelatin was freeze-dried for 20 hours to produce a gelatin-based porous biosponge.
[0055] The preparation process of the sticky barrier layer is as follows: 1) The polymer fibers used in the adhesive barrier layer were prepared by electrospinning a 25% (mass) polycaprolactone (PCL) solution under conditions of high voltage (20 kV), a receiving distance of 20 cm, and a liquid feed rate of 1.5 mL / h. Due to the high viscosity and entanglement between the molecular chains of the 25% PCL solution, polymer fibers with lengths ranging from 100 nm to 500 nm were formed. The PCL solution was prepared using analytically pure (AR) grade ethyl acetate. The fibers formed a PCL polymer fiber membrane by free accumulation on the receiving device. The membrane was then cut into rectangular shapes 4 cm long and 2 cm wide.
[0056] 2) Modification of the bioglue in the adhesive barrier layer: Biomedical-grade gelatin was dissolved in reverse osmosis (RO) water at a mass fraction of 7% in a 65°C water bath. After complete dissolution, the pH of the solution was adjusted to 10.5 using sodium hydroxide (NaOH). Tannic acid was then added to the gelatin solution, and the mixture was stirred in a 50°C water bath for 0.5 hours to produce a cross-linked gelatin solution with a gelatin:tannic acid mass ratio of 1:0.1. After the cross-linked gelatin solution cooled to room temperature, it was evenly coated onto the surface of the prepared PCL polymer fiber membrane. The cross-linked gelatin solution was then placed at 4°C to cool and form a gel on the membrane surface, resulting in a PCL polymer fiber membrane with tissue adhesion properties.
[0057] Taking advantage of the adhesiveness of the gel on the surface of the polymer fiber membrane, the previously prepared gelatin-based porous bio-sponge was directly bonded to the center of the gelatin coating layer of the fiber membrane, and then dried in a vacuum drying oven for 15 hours to obtain the desired self-adhesive composite patch. The present invention has been described in detail above with reference to specific embodiments and exemplary examples. However, these descriptions should not be construed as limiting the present invention. Those skilled in the art will appreciate that various equivalent substitutions, modifications, or improvements may be made to the technical solutions and implementations of the present invention without departing from the spirit and scope of the present invention, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be determined by the appended claims.
Claims
1. A self-adhesive composite patch for repairing tooth extraction socket wounds, characterized in that: The self-adhesive composite patch includes a wound filling layer and an adhesive barrier layer. The wound filling layer is bonded to the middle of the upper surface of the adhesive barrier layer. The wound filling layer is made of biological sponge material, and the adhesive barrier layer is made of polymer fiber and biological glue.
2. The self-adhesive composite patch for tooth extraction socket wound repair according to claim 1, characterized in that: The raw materials for preparing the biological sponge material are selected from one or more of oxidized cellulose, chitosan, starch, polyethylene glycol, polyvinyl alcohol, collagen, gelatin, and tannic acid; and / or, The polymer fiber is made of one or more raw materials selected from polycaprolactone, polylactic acid, polylactic acid-glycolic acid copolymer, polyethylene glycol-caprolactone copolymer, polyamino acid, and polyurethane; and / or, The biological glue is prepared from one or more raw materials selected from oxidized cellulose, chitosan, starch, polyethylene glycol, polyvinyl alcohol, collagen, gelatin and tannic acid.
3. The self-adhesive composite patch for tooth extraction socket wound repair according to claim 2, characterized in that: The biological sponge material is made of gelatin and tannic acid; and / or, The polymer fiber is made of polycaprolactone; and / or, The biological glue is prepared from gelatin and tannic acid.
4. A method for preparing a self-adhesive composite patch for repairing tooth extraction socket wounds according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The biosponge material is made into a wound filling layer, polymer fibers are stacked into a polymer fiber membrane material, and bioglue is coated on the surface of the polymer fiber membrane material to obtain an adhesive barrier layer. The wound filling layer is bonded to the middle of the adhesive barrier layer and then vacuum dried for 10 to 15 hours to obtain a self-adhesive composite patch.
5. The preparation method according to claim 4, characterized in that The preparation method of the wound filling layer comprises the following steps: Gelatin is dissolved in reverse osmosis water at 55-65°C in a water bath with a gelatin mass fraction of 1%-8%. An alkaline solution is added to adjust the pH, and then tannic acid is added and stirred at 40-50°C in a water bath for 0.5-2 hours to carry out a cross-linking reaction to obtain a cross-linked gelatin solution. The mass ratio of gelatin to tannic acid is 1:(0.05-0.10). The cross-linked gelatin solution is then placed in a mold, cooled to room temperature, and frozen at -10--25°C. Finally, it is freeze-dried for 20-30 hours to obtain a gelatin-based porous bio-sponge material, i.e., a wound filling layer.
6. The preparation method according to claim 4, characterized in that The method for preparing the sticky barrier layer comprises the following steps: Step 1: adding polycaprolactone to a solvent and mixing them uniformly to obtain a polycaprolactone solution, and electrospinning the polycaprolactone solution to obtain a polymer fiber membrane material; Step 2: Dissolve gelatin in reverse osmosis water, then add alkaline solution to adjust the pH, and then add tannic acid to carry out a cross-linking reaction to obtain a cross-linked gelatin solution. Apply the cross-linked gelatin solution to the surface of the polymer fiber membrane material, and after cooling, obtain a sticky barrier layer.
7. The preparation method according to claim 6, characterized in that In step 1, Polycaprolactone was added to ethyl acetate and mixed evenly to obtain a polycaprolactone solution with a mass concentration of 15-25%. The polycaprolactone solution was electrospun to obtain polymer fibers with a length of 100 nm to 500 nm. The polymer fibers were accumulated on a receiving device to form a PCL polymer fiber membrane material.
8. The preparation method according to claim 6, characterized in that In step 1, The electrospinning conditions are as follows: voltage of 10-20 kV, receiving distance of 10-20 cm, and liquid feeding speed of 0.5-1.5 mL / h.
9. The preparation method according to claim 6, characterized in that In step 2, Gelatin is dissolved in reverse osmosis water at 55-65°C in a water bath with a gelatin mass fraction of 3%-7%. An alkaline solution is then added to adjust the pH to 9-10.
5. Tannic acid is then added and stirred in a water bath at 40-50°C for 0.5-2h. The mass ratio of gelatin to tannic acid is 1:(0.05-0.10) to obtain a cross-linked gelatin solution.
10. The preparation method according to claim 6, characterized in that In step 2, The cross-linked gelatin solution is evenly coated on the surface of the polymer fiber membrane material, and placed under 0-4°C conditions to allow the cross-linked gelatin solution to cool on the fiber membrane surface to form a gel, thereby obtaining a sticky barrier layer.
Citation Information
Cited By
High-adhesion porous sponge as well as preparation method and application thereof
CN121550470A